Animal Elements on Japanese Kotowaza and the Implementation of Japanese Socio-Cultural Values: A Cognitive Linguistics Point of View - Siti Mafrukha; Dian Bayu Firmansyah; Anggita Stovia (Universitas Dian Nuswantoro, 2021)
This study aims to describe the relationship between the lexical meaning and the idiomatic meaning contained in the Japanese kotowaza and to analyze the level of relevance of each kotowaza to the application of socio-cultural values in Japanese society. This type of research is qualitative descriptive research to describe the meaning of kotowaza through cognitive linguistic studies and conceptual metaphor theory. The data source is a Japanese novel contained in Aozora Bunka. This study found that the animal elements contained in the kotowaza are a conceptualization of attitudes, actions, judgments, circumstances, and feelings. In addition, the city also reflects socio-cultural values that are very relevant to the culture of Japanese society, such as the culture of working hard, being responsible, and being focused and conscientious.